Synthesis and Design of Purpurin-18-Loaded Solid Lipid Nanoparticles for Improved Anticancer Efficiency of Photodynamic Therapy - Sooho Yeo; Hyeon Ho Song; Min Je Kim; Seokhyeon Hong; Il Yoon; Woo Kyoung Lee (MDPI AG, 2022)
Purpurin-18 (P18) is one of the essential photosensitizers used in photodynamic therapy (PDT), but its hydrophobicity causes easy coalescence and poor bioavailability. This study aimed to synthesize P18 and design P18-loaded solid lipid nanoparticles (SLNs) to improve its bioavailability. The characteristics of the synthesized P18 and SLNs were evaluated by particle characteristics and release studies. The effects of P18 were evaluated using the 1,3-diphenylisobenzofuran (DPBF) assay as a nonbiological assay and a phototoxicity assay against HeLa and A549 cell lines as a biological assay. The mean particle size and zeta potential of the SLNs were 164.70-762.53 nm and −16.77-25.54 mV, respectively. These results indicate that P18-loaded SLNs are suitable for an enhanced permeability and retention effect as a passive targeting anti-cancer strategy. The formulations exhibited a burst and sustained release based on their stability. The DPBF assay indicated that the PDT effect of P18 improved when it was entrapped in the SLNs. The photocytotoxicity assay indicated that P18-loaded SLNs possessed light cytotoxicity but no dark cytotoxicity. In addition, the PDT activity of the formulations was cell type- and size-dependent. These results suggest that the designed P18-loaded SLNs are a promising tool for anticancer treatment using PDT.